Fast inactivation of SARS-CoV-2 by UV-C and ozone exposure on different materials - Criscuolo, Elena; Diotti, Roberta A.; Ferrarese, Roberto; Alippi, Cesare; Viscardi, Gabriele; Signorelli, Carlo; Mancini, Nicasio; Clementi, Massimo; Clementi, Nicola (Emerging microbes & infections, 2021)
The extremely rapid spread of the SARS-CoV-2 has already resulted in more than 1 million reported deaths of coronavirus disease 2019 (COVID-19). The ability of infectious particles to persist on environmental surfaces is potentially considered a factor for viral spreading. Therefore, limiting viral diffusion in public environments should be achieved with correct disinfection of objects, tissues, and clothes. This study proves how two widespread disinfection systems, short-wavelength ultraviolet light (UV-C) and ozone (O3), are active in vitro on different commonly used materials. The development of devices equipped with UV-C, or ozone generators, may prevent the virus from spreading in public places.